Lipid characterization of both wild and cultured eggs of cuttlefish (Sepia officinalisL.) throughout the embryonic development - Sykes, António V. (2018)
The present work reports a characterization of mean wet weight and moisture, the lipid class and fatty acid (FA) composition from the total lipids (TL), of both culture and wild eggs of the cuttlefish, Sepia officinalis, throughout the embryonic development. Additionally, reproductive data, such as the number of spawnings, number and mean weight of eggs and duration of spawning period of cultured cuttlefish is provided. Both types of eggs were similar in mean wet weight, moisture content, TL content and lipid composition throughout embryonic development.